Prognostic value of patient‐derived xenograft engraftment in pediatric sarcomas. (9th April 2021) - Castillo‐Ecija, Helena; Pascual‐Pasto, Guillem; Perez‐Jaume, Sara; Resa‐Pares, Claudia; Vila‐Ubach, Monica; Monterrubio, Carles; Jimenez‐Cabaco, Ana; Baulenas‐Farres, Merce; Muñoz‐Aznar, Oscar; Salvador, Noelia; Cuadrado‐Vilanova, Maria; Olaciregui, Nagore G; et al.
Abstract: The goals of this work were to identify factors favoring patient‐derived xenograft (PDX) engraftment and study the association between PDX engraftment and prognosis in pediatric patients with Ewing sarcoma, osteosarcoma, and rhabdomyosarcoma. We used immunodeficient mice to establish 30 subcutaneous PDX from patient tumor biopsies, with a successful engraftment rate of 44%. Age greater than 12 years and relapsed disease were patient factors associated with higher engraftment rate. Tumor type and biopsy location did not associate with engraftment. PDX models retained histology markers and most chromosomal aberrations of patient samples during successive passages in mice. Model treatment with irinotecan resulted in significant activity in 20 of the PDXs and replicated the response of rhabdomyosarcoma patients. Successive generations of PDXs responded similarly to irinotecan, demonstrating functional stability of these models. Importantly, out of 68 tumor samples from 51 patients with a median follow‐up of 21.2 months, PDX engraftment from newly diagnosed patients was a prognostic factor significantly associated with poor outcome ( p = 0.040). This association was not significant for relapsed patients. In the subgroup of patients with newly diagnosed Ewing sarcoma classified as standard risk, we found higher risk of relapse or refractory disease associated with those samples that produced stable PDX models ( p = 0.0357). Overall, our study shows that PDX engraftment predicts worse outcome in newly diagnosed pediatric sarcoma patients.